Effect of China national centralized drug procurement policy on anticoagulation selection and hemorrhage events in patients with AF in Suining - Zhang, Qi; Wang, Ruili; Chen, Lei; Chen, Wensu (Frontiers in Pharmacology, 2024)
Background: Launched in March 2019, the National Centralized Drug Procurement (NCDP) initiative aimed to optimize the drug utilization framework in public healthcare facilities. Following the integration of Non-Vitamin K Antagonist Oral Anticoagulants (NOACs) into the procurement catalog, healthcare establishments in Suining swiftly transitioned to the widespread adoption of NOACs, beginning 1 March 2020. Objective: This study aims to comprehensively assess the impact of the NCDP policy on the efficacy of anticoagulation therapy, patient medication adherence, and the incidence of hemorrhagic events in individuals with non-valvular atrial fibrillation (NVAF) residing in Suining. The analysis seeks to elucidate the broader impacts of the NCDP policy on this patient demographic. Methods: This study analyzed patient hospitalization records from the Department of Cardiology at Suining County People’s Hospital, spanning 1 January 2017, to 30 June 2022. The dataset included demographic details (age, sex), type of health insurance, year of admission, hospitalization expenses, and comprehensive information on anticoagulant therapy utilization. The CHA2DS2-VASc scoring system, an established risk assessment tool, was used to evaluate stroke risk in NVAF patients. Patients with a CHA2DS2-VASc score of 2 or higher were categorized as high-risk, while those with scores below 2 were considered medium or low-risk. Results: 1. Treatment Cost Analysis: The study included 3,986 patients diagnosed with NVAF. Following the implementation of the NCDP policy, a significant increase in the average treatment cost for hospitalized patients was observed, rising from 8,900.57 ± 9,023.02 CNY to 9,829.99 ± 10,886.87 CNY (p < 0.001). 2. Oral Anticoagulant Utilization: Overall, oral anticoagulant use increased from 40.02% to 61.33% post-NCDP (p < 0.001). Specifically, NOAC utilization among patients dramatically rose from 15.41% to 90.99% (p < 0.001). 3. Hemorrhagic Events: There was a significant decrease in hemorrhagic events following the NCDP policy, from 1.88% to 0.66% (p = 0.01). Hypertension [OR = 1.979, 95% CI (1.132, 3.462), p = 0.017], history of stroke [OR = 1.375, 95% CI (1.023, 1.847), p = 0.035], age ≥65 years [OR = 0.339, 95% CI (0.188, 0.612), p < 0.001], combination therapy of anticoagulants and antiplatelets [OR = 3.620, 95% CI (1.752, 7.480), p < 0.001], hepatic and renal insufficiency [OR = 4.294, 95% CI (2.28, 8.084), p < 0.001], and the NCDP policy [OR = 0.295, 95% CI (0.115, 0.753), p = 0.011] are significant risk factors for bleeding in patients with atrial fibrillation. 4. Re-hospitalization and Anticoagulant Use: Among the 219 patients requiring re-hospitalization, there was a notable increase in anticoagulant usage post-NCDP, from 36.07% to 59.82% (p < 0.001). NOACs, in particular, saw a substantial rise in usage among these patients, from 11.39% to 80.92% (p < 0.001). 5. Anticoagulant Type Change: The NCDP policy [OR = 28.223, 95% CI (13.148, 60.585), p < 0.001] and bleeding events [OR = 27.772, 95% CI (3.213, 240.026), p = 0.003] were significant factors influencing the alteration of anticoagulant medications in patients. Conclusion: The NCDP policy has markedly improved anticoagulation management in patients with AF. This policy has played a crucial role in enhancing medication adherence and significantly reducing the incidence of hemorrhagic events among these patients. Additionally, the NCDP policy has proven to be a key factor in guiding the selection and modification of anticoagulant therapies in the AF patient population.